2015
DOI: 10.1086/682907
|View full text |Cite
|
Sign up to set email alerts
|

Deployments, Combat Exposure, and Crime

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 70 publications
2
16
0
Order By: Relevance
“…The ubiquity of these tales across time and place suggests that people are captivated by the issue of war’s impact on the soldiers who fight them and the communities to which they return. 1 This is no less true of scholars who have examined in great quantity and depth everything from the effects of combat experience on violence, domestic abuse, and criminal behavior (recent examples include Anderson & Rees, 2015; Cesur & Sabia, 2016; Gartner & Kennedy, 2018; MacManus et al, 2015; Teachman & Tedrow, 2016) to the physical and mental health effects of wartime service (recent examples include Griffith, 2019; Godfrey et al, 2015; Lee et al, 2019; Nassif et al, 2019) to how combat might impact the political attitudes and behavior of veterans (Blattman, 2009; Grossman et al, 2015; Horowitz & Stam, 2014; Teigen, 2006). Given the demanding tempo of military operations since 9/11—with the United States alone having deployed roughly 3 million troops over the last 20 years (Wenger et al, 2018)—it is particularly important to understand how war impacts veterans and how they, in turn, affect our society.…”
mentioning
confidence: 99%
“…The ubiquity of these tales across time and place suggests that people are captivated by the issue of war’s impact on the soldiers who fight them and the communities to which they return. 1 This is no less true of scholars who have examined in great quantity and depth everything from the effects of combat experience on violence, domestic abuse, and criminal behavior (recent examples include Anderson & Rees, 2015; Cesur & Sabia, 2016; Gartner & Kennedy, 2018; MacManus et al, 2015; Teachman & Tedrow, 2016) to the physical and mental health effects of wartime service (recent examples include Griffith, 2019; Godfrey et al, 2015; Lee et al, 2019; Nassif et al, 2019) to how combat might impact the political attitudes and behavior of veterans (Blattman, 2009; Grossman et al, 2015; Horowitz & Stam, 2014; Teigen, 2006). Given the demanding tempo of military operations since 9/11—with the United States alone having deployed roughly 3 million troops over the last 20 years (Wenger et al, 2018)—it is particularly important to understand how war impacts veterans and how they, in turn, affect our society.…”
mentioning
confidence: 99%
“…Of particular concern is the fact that military troops return specifically to military bases and the timing of this return is used for the construction of the variable eqp t . Numerous studies have shown that conscription into the military and exposure to combat situations may have subsequent effects on violent and criminal behavior (Rohlfs (2010); Galiani, Rossi and Schargrodsky (2011); Sreenivasan et al (2013); Anderson and Rees (2015); 15 Results are reported in Table 2 comparing column "Treated (1)" with "Not Treated (3)". I address this issue in an empirical framework where the only comparison used to identify the effect of militarization on violent crime is between police departments that differ in the closeness to disposition centers, and not in their closeness to a military base.…”
Section: The 1033 Program and Data Sourcesmentioning
confidence: 99%
“…Another example is Dohrenwend et al (2004), who document that 70.9% of the US male Vietnam veterans appraised the impact of their service on their present lives as mainly positive. For military service during the AVF era, Anderson and Rees (2015) document that units that were never-deployed contributed more to community violent crime (for instance, murders and rapes) relative to the contribution of the units that were deployed. The positive impacts of violence exposure on post-military service life may be explained by the posttraumatic growth xxvii effect of wartime combats on veterans (Maguen et al, 2006;Forstmeier et al, 2009), which may in addition improve veterans' post-service adaptation to civilian life and reduce their tendency to commit crimes.…”
Section: Vb3 Additional Analysis On the Effect Of Military Service mentioning
confidence: 99%